Moderasi Aliran Kas Bebas terhadap Hubungan Rasio Pembayaran Dividend dan Pengeluaran Modal dengan Earnings Response Coefficient - ALI SANI UYARA; ASKAM TUASIKAL (The Indonesian Journal of Accounting Research, 2013)
Free cash flow is cash flow in excess of that required to fund all projects that have positive net present values when discounted at the relevant cost of capital. Jensen hypothesized that price will increase in payouts to shareholders (or promises to do so), and prices will fall with reductions in payments or new requests for funds (or reduction in promises to make future payments). The validation of this hypothesis examined by prior research on dividend and capital spendingThis study was motivated by the results of most research examined the usefulness of earnings and cash flow. The research found that the information of earnings and cash flow didn’t have information contents.The objective of this study examines the impact of free cash flow on association both dividend payout and capital spending by earnings response coefficients. The contributions of this study are twofold. First, suggesting the investors to use free cash flow when they predict stocks price or stocks return. Second, enriching literature on finance field.The hypothesis was tested by multiple regressions analysis for 46 firms with 95% confidence interval. Free cash flows are measured with method of Ross et al. (2000). The earnings response coefficients are measured by using Firm-Specific Coefficients Methodology (FSCM).This study provides evidence that free cash flow has an impact on the association of dividend payout ratio to earnings response coefficients, but it hasn’t impact on the association of capital spending to earnings response coefficients.